PENGARUH CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA RESTORAN SEDERHANA KOTA TELUK KUANTAN - Ega Minata Prayunita; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Purchasing decisions are an important part of the product marketing concept, this is the background of this research. Implementing a good brand image in front of consumers and the right service quality are part of the factors supporting consumer purchasing decisions. This strategy is applied by Sederhana Restaurant Teluk Kuantan City. This study aims to determine the effect of Brand Image and Service Quality on purchasing decisions at Sederhana Restaurant Teluk Kuantan City. The method used in this research is descriptive and quantitative, with the source of the data from this study coming from primary data obtained through the interview process and distributing questionnaires which were then tested statistically through the SPSS program and secondary data using product sales data for Sederhana Restaurant Teluk Kuantan City from 2016-2020. The analytical method used in this research is simple and multiple regression analysis, and through validity and reliability tests. In this study the results obtained are that the Brand Image (X1) has a positive and significant effect on Purchase Decisions (Y), Service Quality (X2) has a positive and significant effect on Purchase Decisions (Y).Keywords: Brand Image, Service Quality and Purchase Decision